Antibacterial cellulose acetate films incorporated with N‐halamine‐modified nano‐crystalline cellulose particles. (15th September 2016) - Liu, Ying; Li, Lin; Pan, Nengyu; Wang, Yingfeng; Ren, Xuehong; Xie, Zhiwei; Buschle‐Diller, Gisela; Huang, Tung‐Shi
Abstract : Cellulose acetate (CA) membranes have been widely used as food packaging materials as well as reverse osmosis systems. This study presents the manufacturing of composite CA film with antibacterial properties which is essential for CA film applications in the industry. N ‐Halamine precursor of polymethacrylamide‐modified nano‐crystalline cellulose particles (NCC‐PMAMs) were prepared and incorporated into CA film. The composite films with intercalated structure were formed via a solvent‐casting technique. After chlorination, the composite film CA/NCC‐PMAM‐Cl‐1.0 with 1.82 × 10 16  atoms/cm 2 covalently bonded chlorine showed excellent antibacterial properties by inactivating 6.04 logs of Staphylococcus aureus and 6.27 logs of Escherichia coli within 10 and 5 min, respectively. According to X‐ray diffraction spectra, NCC‐PMAMs behaved as a facilitator for film crystallization. The mechanical strength of the composite film also increased compared with that of pure CA film. However, the composite film became brittle and the maximum decomposition temperature decreased slightly. Preliminary data of in vitro cytocompatibility evaluation indicate that the film is not toxic and has potential use in food packaging. Copyright © 2016 John Wiley & Sons, Ltd.